Peningkatan Hasil Belajar Siswa Melalui Model Pembelajaran E-Learning Dengan Media Google Meet - Permatasari, Carolina Lita (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2022)
Abstract: This research is an effort to improve science learning outcomes through an e-learning model using google meet media for class VIII-1 of Marsudirini Tualang Junior High School. This is because many students do not understand the teacher through google meet. The provision of learning materials delivered by the teacher through google meet causes science learning outcomes to be relatively low or stil below minimum completeness criteria, which is 70. This study uses classromm action research in the form of implementing e-learning model with google meet media with the aim of improving student learning outcomes for class VIII-1 Marsudirini Tualang Junior High School which consists of two cycles and each cycle consists of planning, implementing, observing, and reflecting. The research subjects were students of class VIII-1 Marsudirini Tualang Junior High School. The number of students is 28 students consisting of 14 male students and 14 female students. The results showed that the application of the e-learning model with google meet media could improve science learning outcomes for class VIII-1 students of Marsudirini Tualang Junior High School. Judging from the results of the pre-cycle students who completed minimum completeness criteria, only 12 students (42,8%) and 16 students (57,2%) who had not. In the first cycle there are 17 students (60,7%) who have completed and 11 students (39,3%) have not completed, and in the second cycle there are 25 students (89,2%) who have completed and there are 3 students (10,8%) unfinished. From the improve in learning outcomes, this classroom action research was stopped in cycle II because it had reached the classical completeness criteria, namely 85% of the total number of students who had completed learning and were declared successful in improving science learning outcomes for class VIII-1 students of Marsudirini Tualang Junior High School. Keywords: Students learning outcomes, E-learning model, Google Meet media